answer this question correctly
Attachments:
![](https://hi-static.z-dn.net/files/d0b/13406ee31e61eb4687f855210e342c1c.jpg)
Answers
Answered by
0
Answer : 2x² - 5x/6 + 1/12
= 2x² - 5x/6 + 12
= 2x² - 5x + 2
= 4x - 5x + 2
x = (-4) +5 +2
x = (-4) + 7
x = -3
Answered by
1
Answer:
Hope this helps u!!!.........
Attachments:
![](https://hi-static.z-dn.net/files/d59/5095ccf52f4679c2184d479d42107aba.jpg)
Similar questions
Math,
3 months ago
Science,
3 months ago
Accountancy,
3 months ago
English,
7 months ago
Accountancy,
7 months ago
Math,
1 year ago
Math,
1 year ago